Neillia daloushanensis, a new species of Neillia (Rosaceae) from southwest China - Xu Wu; Dai-Kun Ma; Ming-Tai An; Yu-Cai Feng; Jiang-Hong Yu; Ji-Huai Han (PhytoKeys)
Through detailed morphological comparison and robust molecular evidence, we confirm Neillia daloushanensis M.T.An & Xu Wu as a new species of Rosaceae from Guizhou province, southwest China. Morphologically, N. daloushanensis closely resembles N. gracilis but differs in several key traits: it is a creeping liana rather than a low subshrub; its stems are 0.6–1.5 cm long compared to the slender stems less than 0.5 cm tall in N. gracilis; its leaves are larger, measuring 5–9 × 3–6 cm vs. 2.5–3.5 × 2–3 cm; stipules are sessile, clasping, and larger (0.8–1.3 × 0.6–1.1 cm) rather than peitiolate and smaller (0.4–0.6 × 0.3–0.5 cm) without clasping; calyx tubes are densely pilose on both surfaces and bear stipitate glands abaxially, in contrast to the slightly pubescent, glandless calyx tubes of N. gracilis; and the seed number ranges from 2 to 4 instead of consistently 2. These morphological distinctions are further corroborated by molecular phylogenetic analysis based on 703 single-copy nuclear genes, supporting the recognition of N. daloushanensis as a distinct species within the genus.